Applying an auction optimization algorithm to mobile edge computing for security. Issue 10 (9th November 2021) - Wang, Yi; Tang, Tao; Jiang, Fang; Xu, Yaohua; Li, Liping; Huang, Rong
Abstract: The great demand for mobile blockchain computing power is often unsatisfied by terminal devices, so computational tasks are offloaded to edge computing servers. This paper proposes a new mobile communication blockchain assumption, forms a computing power alliance (CPA), and builds a smart contract‐based security model. First, mining difficulty compensates for the personal computing power outside the CPA to increase the block generation difficulty. Second, contract account funds are used to increase the cost of malicious nodes seeking to launch forking attacks, and the duration is used to limit mining. Finally, a court trial is opened to select validators to verify the fork. The auction algorithm is used to allocate computing power in the CPA, and a price utility function is constructed to maximize social welfare. The joint optimization algorithm increases the transaction price and improves the system security. Simulation results verify that the system security increases with the blocked funds and duration, and the forking attack success rate approaches zero as the number of validators increases. The proposed algorithm provides considerable sum utility and average revenue gains versus traditional methods under different numbers of mobile users and computational capabilities, and the security of the algorithm is also higher.